"Non‐coercive Rearrangements": Theorizing Desire in TESOL. Issue 2 (1st August 2013) - Motha, Suhanthie; Lin, Angel
Abstract : In this article, the authors argue that at the center of every English language learning moment lies desire: desire for the language; for the identities that English represents; for capital, power, and images that are associated with English; for what is believed to lie beyond the doors that English unlocks. However, despite its centrality within TESOL practice, the construct of desire has been largely undertheorized by English language educators. The authors propose (1) that educators in the TESOL field would benefit from a greater recognition of desire as situated and co‐constructed, acknowledging that our desires are not solely our own but are intersubjectively constituted and shaped by our social, historical, political, institutional, and economic contexts; (2) that the difference between conscious and unconscious desire is significant in language learning; and (3) that whereas desire can be manipulated in exploitative or unethical ways, it can also, given the right circumstances, serve as a tool for compassionate and liberatory pedagogy. This article explores the interconnectedness of desire with motivation and investment, the commodification of English, akogare desire, racial identities, globalizing forces, colonialism, and communicative language teaching. The authors propose a revisioning of TESOL that recognizes the centrality of desire in the acquisition of English.